PECULIARITIES OF THE TECHNOLOGY OF CONTINUOUS CASTING OF SLUGS OF MACHINE- AND MACHINE-TOOL-BUILDING - E. B. Demchenko; E. I. Marukovich (Литьë и металлургия, 2006)
The peculiarities of technology of continuous casting of ingots of machine- and machine tool building are shown. At development of technology it is necessary to subject the nomenclature of ingots to analysis in order to reveal expediency of their production by means of continuous casting.